Study of essential oil composition of Pyrethrum pulchrum Ledeb. - E, Uugangerel; G, Choijamts; D, Enkhmaa (Bulletin of the Institute of Chemistry and Chemical Technology, 2018)
Pyrethrum pulchrum an impressive flower growing on large-stoned screes at the snow line, usually on glacier moraines in the mountains of Central Asia and South Siberia. The purpose of this study was to determine the essential oil composition from the aerial part of Pyrethrum pulchrum growing in Mongolia. The essential oil was obtained by hydro distillation and it had yield determined 0.1%. The oil was analyzed by GC-MS techniques. Fifty-seven components were identified representing 99.98% of the total oil composition. The main compounds of essential oil were camphor (33.9%), linalool (21.1%), α-pinene (9.0%), (Z)-γ-Curcumyl 2-methylbutyrate (4.82%), pentylcurcumene (3.21%), camphene (2.85%), tricosane (2.78%), nerolidol (2.63%), α-selinene (1.8%) and β-penine (1.4%). To our best knowledge, no previous studies have been reported on the chemical composition of the essential oil of Pyrethrum pulchrum. Дэгжин шиваантиг (Pyrethrum pulchrum Ledeb.) ургамлын эфирийн тосны химийн найрлагын судалгаа Хураангуй: Дэгжин шиваантиг (Pyrethrum pulchrum Ledeb.) нь Төв Ази болон Өмнөд Сибирийн уулархаг бүс нутгийн хад асгатай өндөр уулын бүслүүрт тархан ургадаг цэцэгт ургамал юм. Бид Монгол оронд ургадаг Дэгжин шиваантиг ургамлын газрын дээд хэсгийн эфирийн тосны химийн найрлагыг тодорхойллоо. Эфирийн тосыг усны уураар нэрж гарган авахад гарц 0.1% байв. Хийн хроматограф-масс спектрометрийн аргаар эфирийн тосны найрлаганд нийт 57 нэгдэл тодорхойлогдсон ба камфор (33.9%), линалоол (21.1%), α-пенин (9.0%), (Z)-γ-куркумил-2-метилбутират (4.82%), пентилкуркумен (3.21%), камфен (2.85%), трикосан (2.78%), неролидол (2.63%), α-селин (1.8%) ба β-пенин (1.4%) зэрэг нэгдлүүд зонхилон агуулагдаж байв. Энэхүү судалгааны ажил нь Дэгжин шиваантиг ургамлын эфирийн тосны судалгааг анх удаа хийж, танилцуулж буйгаар онцлог юм. Түлхүүр үгс: Нийлмэл цэцэгтэн , Дэгжин шиваантиг, Марал цэцэг, эфирийн тос